Problem Identification of Marine Cadastre in Indonesian Archipelagic Perspective - Astor, Yackob; Nugraha Sulasdi, Widyo; Wisayantono, Dwi; Hendriatiningsih, Sadikin (Indonesian Journal of Geospatial, 2014)
Abstract. Indonesia as an archipelagic country has marine area larger than land area, 13.446 islands (Geospatial Information Agency, 2012) with coastline 95,181 km (Indonesian Maritime Council, 2008), making Indonesia has natural resources of the sea more than the natural resources on land. This potential conditions of marine resources is seen as an opportunity for Indonesia as a developing country to build excellence in coastal and marine field. But during 68 years of the nations independence, maritime sector has notproved as a sector that can be seeded by the nation and relied by Indonesian people. Based on the literature, one of the main problems in Indonesian ocean is marine boundariesdetermination are unclear and unresolved causes uncontrolled human intervention in managing marine resources and chaotic patterns of use of marine resources, uncontrolled utilization even destructive.Â Â This paper discusses about marine boundaries problems that is happened in Indonesia whether they arise from the country and from abroad. Until now much of Indonesia marine boundaries with neighboring countries are still unfinished. Implementation of UUD1945 Article 18 and 25 junctoLaw No.32/2004 juncto Regulation of the ministry of home affairs No. 1/2006 about determination and demarcation of boundaries (including marine boundary) hasnâtrealized. There is no certaintboundaries of exploitation and utilization activities in ocean spacebyinstitutional (sector), nor implementation of marine management in eastern Indonesia that more often faced with the existence of customary marine management caused overlapping claims marine areas that can raisemarine boundariesconflicts between regions, sectors or customary.Â Â In general, marine cadastre deals with how states define, organize and manage marine boundaries in their countries. This condition causes marine cadastre concepts in continental countries such as America, Canada, and Australia can not be fully implemented in Indonesia. Marine cadastre concept for Indonesia should adopt the archipelago needs, in the context associated with UNCLOS82, Law No. 32 2004 about regional autonomy, Law No.27 2007 about coastal management areas and small islands, and customary marine authority. This paper is part of dissertation research in order to build model of marine cadastre system uses evaluation definition approach and geospatial information principles.Â Â Keywords: Marine Boundaries, Marine Cadastre, Archipelagic Perspective